Exploring the Multifaceted Potential of a Peptide Fraction Derived from Saccharomyces cerevisiae Metabolism: Antimicrobial, Antioxidant, Antidiabetic, and Anti-Inflammatory Properties - Patrícia Branco; Elisabete Muchagato Maurício; Ana Costa; Diogo Ventura; Catarina Roma-Rodrigues; Maria Paula Duarte; Alexandra R. Fernandes; Catarina Prista (MDPI AG, 2023)
The rising demand for minimally processed, natural, and healthier food products has led to the search for alternative and multifunctional bioactive food components. Therefore, the present study focuses on the functional proprieties of a peptide fraction derived from Saccharomyces cerevisiae metabolism. The antimicrobial activity of the peptide fraction is evaluated against various foodborne pathogens, including Candida albicans, Candida krusei, Escherichia coli, Listeria monocytogenes, and Salmonella sp. The peptide fraction antioxidant properties are assessed using FRAP and DPPH scavenging capacity assays. Furthermore, the peptide fraction's cytotoxicity is evaluated in colorectal carcinoma and normal colon epithelial cells while its potential as an antidiabetic agent is investigated through α-amylase and α-glucosidase inhibitory assays. The results demonstrate that the 2-10 kDa peptide fraction exhibits antimicrobial effects against all tested microorganisms, except C. krusei. The minimal inhibitory concentration for E. coli, L. monocytogenes, and Salmonella sp. remains consistently low, at 0.25 mg/mL, while C. albicans requires a higher concentration of 1.0 mg/mL. Furthermore, the peptide fraction displays antioxidant activity, as evidenced by DPPH radical scavenging activity of 81.03%, and FRAP values of 1042.50 ± 32.5 µM TE/mL at 1.0 mg/mL. The peptide fraction exhibits no cytotoxicity in both tumor and non-tumoral human cells at a concentration up to 0.3 mg/mL. Moreover, the peptide fraction presents anti-inflammatory activity, significantly reducing the expression of the TNFα gene by more than 29.7% in non-stimulated colon cells and by 50% in lipopolysaccharide-stimulated colon cells. It also inhibits the activity of the carbohydrate digestive enzymes α-amylase (IC50 of 199.3 ± 0.9 µg/mL) and α-glucosidase (IC20 of 270.6 ± 6.0 µg/mL). Overall, the findings showed that the peptide fraction exhibits antibacterial, antioxidant, anti-inflammatory, and antidiabetic activity. This study represents a step forward in the evaluation of the functional biological properties of S. cerevisiae bioactive peptides.